Construction of Reference Chromosome-Scale Pseudomolecules for Potato: Integrating the Potato Genome with Genetic and Physical Maps - Sharma, SK (2013)
Proyecto FEMCIDI-OEA SEDI/AE-305 /09 (2008-2012), Proyecto Bilateral Argentina, Per; FINCyT (099-FINCyT-EQUIP-2009) / (076-FINCyT-PIN-2008), Prestamo BID no. 1663/OC-PE, Instituto Nacional de Innovacion Agraria, Ministry of Agriculture of Peru, Peruvian Ministry of Agriculture, Technical Secretariat of coordination with the CGIAR, Consejo Nacional de Ciencia, Tecnologia e Innovacion Tecnologica, Peru (CONCYTEC), Special Multilateral Fund of the Inter-American Council for Integral Development (FEMCIDI-Peru).